Immigrants, Racial Citizens, and the (Multi)Cultural Politics of Neoliberal Los Angeles - Kim, Jinah (Social justice, 2008)
Part of a special issue on Asian and Pacific Islander populations within the U.S. The writer critiques dominant multicultural discourses operating within the U.S. currently. She refocuses debate about the black-white divide in Los Angeles to include both Central American and Asian immigrants who cannot be codified using these terms. She argues that neoliberal discourse of multiculturalism is inadequate in meeting the challenges posed by events like Los Angeles' 1992 race riots.